Effects of 8-week high intensity maximal aerobic speed training combined with change of direction (COD) improving VO2max of 16-year-old players - Bici, A.; Hafizi, A.; Skenderi, D. (World Congress of Performance Analysis of Sport XII, 2018)
The purpose of the present study show the effects of HIIT Maximal Aerobic Speed training at intensity of 120% of MAS but with Change of Direction (COD). Responses in Heart Rate (HR) and maximal oxygen uptake VO2max were examined. Eighteen soccer player Age 16 year old of Football School were divided in two groups, one Test Group and the other Control Group. The Test group participated for 8 weeks in the running circuit 125m with direction change 90 grade (45m) -180 grade (25m) -360 grade (5m) -180 grade (25m) -45 grade (25m). Realization time is 30 sec. Time between breaks is 4.30 min. The Series is 1x. Number of Repeats is First Week 4 Times. Second Week 5 Times and Four Weeks Left 6 Times. Volume 4 Times - 500 meter. 5 Times- 625 meter. 6 Times - 750 meter. Frequency and Duration of Exercise is 3 times a week for 8 weeks. The speed of running 120% of MAS: 3.6m / s (100% SHMA) * 120% = 4.33 m / s. The control group assigned according the annual plan, aerobic resistance long slow distance training protocol. Result of Test Group show. HR lowering moderately by 3% and V02 Max in Astrand Test 6` increased by 7% and Cooper Test 12` by 12.9 %. From 11 soccer player of Test Group. 50% of them increased in meters covered in the Second Copper Test by 240-280 meter. 20% 140-190 meter and 30% 50-90 meter. The Control Group show increase in VO2 Max in Astrand Test 6` by 8 % and Cooper Test 12` by 4.5 %. From 7 soccer player of Control Group. 20% of them increased in meters covered in the Second Copper Test by 250 meter, 40% 140-170 meter and 40% 50-90 meter. Conclusion: High Intensity Maximal Aerobic Speed Training combined with Change of Direction (COD) boost V02max of soccer player improving soccer performance by increasing the distance covered in Cooper Test 12`.